A model of business ethics - Garzón Castrillon, Manuel Alfonso (2020)
This article aimed to establish the background of ethics and business ethics,through content analysis, with a qualitative approach, descriptive review anddocument search, was carried out in several stages:, inquiry of scientific articles,the organization of information and writing, different definitions of ethics andbusiness ethics are addressed and a definition is proposed, and model of businessethics is proposed and conclusions are reached.